Formulation of criterion functional and set of constraints in problems of physical settings designing - Prokhorets, I.M.; Prokhorets, S.I.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2004)
Characteristics of semiconductor spectrometer and neutronography setting were investigated using system analysis methods.